THE ROLE OF SOCIAL WORKERS IN IN CREASING THE INDEPENDENT LIFE OF PERSONS WITH VIEW DISABILITIES - Hobarth Williams Soselisa (Fakultas Ilmu Sosial dan Ilmu Politik, 2023)
This article aims to explain the roles of social workers in increasing the independence of life for people with visual disabilities. Persons with disabilities are a group of people who have limitations that can hinder their participation and participation in social life. Disability is a limitation experienced by a person with their environment, not just physically or mentally, but is a multi-dimensional phenomenon consisting of bodily functions, activity limitations, barriers to participation and environmental factors. Social workers as a humanitarian aid profession have access to and a role in providing social services to persons with disabilities. There are problems with persons with disabilities, social workers have a professional responsibility in providing services and interventions for persons with disabilities. The social work intervention in this case aims to achieve social functioning with disabilities.